Efficacy of Plasma free Hemoglobin for detecting centrifugal pump thrombosis. (September 2021) - Kuroda, Taiyo; Mutsuga, Masato; Yamada, Masao; Yamakawa, Masato; Yuhara, Satoshi; Hasegawa, Hiroki; Yokote, Jun; Yokoyama, Yukifusa; Yamada, Tetsuya; Koyama, Tomio; Usui, Akihiko
Introduction: Lactate dehydrogenase (LDH) is widely used as an indicator of pump thrombosis in a centrifugal pump. However, due to the low specificity of LDH, pump thrombosis is difficult to detect in the clinical environment. We measured plasma free hemoglobin (pfHb) with the portable device in ICU. The goal of this investigation is to evaluate its diagnostic ability for pump thrombosis. Methods: We enrolled 31 consecutive patients who needed Extracorporeal Membrane Oxygenation (ECMO) therapy and pfHb was determined with HemoCue ® plasma/Low Hb photometer. Pump thrombosis was analyzed macroscopically at the timing of pump explantation or exchange. Also, we divided the pump thrombosis into a grading scale by the place of thrombosis. Results: The median of peak pfHb was significantly lower in the none thrombus group (0.03 g/dL) than that of in the thrombus group (0.05g/dL) ( p = 0.01). In our grading criteria, pfHb was significantly higher when the thrombus is existing near the shaft ( p = 0.015). Contrary, no significant difference was found for LDH. The ROC analysis of pfHb revealed an AUC of 0.77 for detecting pump thrombosis with the best statistical cutoff value at 0.05 g/dL (specificity, 78%; sensitivity, 77%). Also, ROC analysis of LDH was performed (AUC, 0.44; cutoff value, 1200 IU/L; specificity, 59%; sensitivity, 54%) and compared with pfHb. AUC was significantly higher in pfHb ( p = 0.04). Conclusion: Our results showed the efficacy of pfHb for detecting centrifugal pump thrombosis.